2023
DOI: 10.3390/antiox12040811
|View full text |Cite
|
Sign up to set email alerts
|

Oxidants and Cardiorenal Vascular Remodeling—Insights from Rare Genetic Tubulopathies: Bartter’s and Gitelman’s Syndromes

Abstract: Two human genetic tubulopathies, Bartter’s (BS) and Gitelman’s (GS) syndromes, have normo/hypotension and absent cardiac remodeling despite their apparent angiotensin system (RAS) activation. This seeming contradiction has led to an extensive investigation of BSGS patients, the result of which is that BSGS represents a mirror image of hypertension. BSGS’s unique set of properties has then permitted their use as a human model to probe and characterize RAS system pathways and oxidative stress in cardiovascular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…On the contrary, good glycemic control improved their effect ameliorating cardiac remodeling and enhancing the good branch of RAAS [102]. This is in line with the absence of cardiac remodeling observed in BS/GS patients [19]: indeed, they present low levels of glycosylated ACE2, probably due to their metabolic alkalosis and likely impairing the cellular glycosylation process [29].…”
Section: Heartsupporting
confidence: 60%
See 1 more Smart Citation
“…On the contrary, good glycemic control improved their effect ameliorating cardiac remodeling and enhancing the good branch of RAAS [102]. This is in line with the absence of cardiac remodeling observed in BS/GS patients [19]: indeed, they present low levels of glycosylated ACE2, probably due to their metabolic alkalosis and likely impairing the cellular glycosylation process [29].…”
Section: Heartsupporting
confidence: 60%
“…Several studies from our group reported a strong activation of the ACE2/Ang 1-7/MasR axis in BS/GS patients, coupled with a reduced expression of proteins involved in the oxidative stress (as p22 phox ), reduced activation of the RhoA/Rho-kinase pathways, increase NO production and endothelial protection [15,18,19,78]. A comparative study between normotensive, hypertensive, and BS/GS patients reported that the p63RhoGEF, both at mRNA and protein level and MYPT-1 phosphorylation status were higher in hypertensive patients and lower in BS/GS patients compared to controls [79] (Figure 2).…”
Section: Oxidative Stressmentioning
confidence: 91%